THE EFFECT OF ENTREPRENEURIAL ATTITUDE AND MANAGER'S BUSINESS ABILITY ON SMEs ORGANIZATIONAL PERFORMANCE - Dewi, Liliana; Christian, Sonata (Jurnal Entrepreneur dan Entrepreneurship, 2017)
This study aims to explain (1) the effect of entrepreneurial attitude of SME managers on SME organizational performance and (2) the effect of business manager’s ability on SME organizational performance. Data are collected using questionnaires with a sample size of 35 respondents. The data come from the respondents as SME owners or representatives who are familiar with the SME operational and management activities. Research data are processed using multiple regression analysis. The results show that entrepreneurship attitude has an effect on the performance of SME organization, while business ability has no effect at all.